An investigation of L2 reading comprehension of linear texts and hypertexts and working memory capacity - Fontanini, Ingrid (2007)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.